"I Intend Therefore to Prorogue": the effects of political conflict and the Glorious Revolution in parliament, 1660–1702. (15th March 2018) - Dimitruk, Kara
Abstract: This paper provides evidence that the Glorious Revolution removed political barriers to changing property rights in seventeenth century England. I study parliament's passage of estate bills, a legislation that broke restrictions on land use and made up most of parliament's legislative output from 1660 to 1702. Using a new dataset on estate bills, I first document that the sudden closure (prorogation) of parliament by the monarch caused bills to fail. Probit and OLS estimates show estate bills were 19 percentage points more likely to fail in these sessions. Second, I show conflict delaying revenue bills and conflict with the monarch's interests made sudden prorogations more likely before the Glorious Revolution. Political and constitutional changes with the Glorious Revolution were thus important for England's economic development. They improved parliament's provision of legislation that made property rights more flexible to changing economic opportunities throughout the preindustrial era.